2004
DOI: 10.1111/j.1931-2393.2004.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Commercial Sex Workers Among Hispanic Migrants In North Carolina: Implications for the Spread of HIV

Abstract: CONTEXT: Rates of HIV and AIDS have risen among U.S. Hispanics and in migrant‐sending regions of Mexico and Central America, pointing to a link between migration and HIV. However, little is known about male migrants' sexual risk behaviors, such as the use of commercial sex workers. METHODS: The prevalence and frequency of commercial sex worker use was examined among 442 randomly selected Hispanic migrants in Durham, North Carolina. Logistic and Poisson regression techniques were used to model predictors of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 10 publications
(3 reference statements)
2
50
4
Order By: Relevance
“…Variation of rates is likely due to differences in the characteristics of the study populations or the context within which they live. For example, engaging in sex with a FSW is more common among single migrant men compared to married migrant men [23] and among unaccompanied married men compared to married men who are accompanied [26]. There is some evidence that FSW patronage may be more frequent when migrants arrive and decrease over time [17,25].…”
Section: Latinos and Hivmentioning
confidence: 95%
See 2 more Smart Citations
“…Variation of rates is likely due to differences in the characteristics of the study populations or the context within which they live. For example, engaging in sex with a FSW is more common among single migrant men compared to married migrant men [23] and among unaccompanied married men compared to married men who are accompanied [26]. There is some evidence that FSW patronage may be more frequent when migrants arrive and decrease over time [17,25].…”
Section: Latinos and Hivmentioning
confidence: 95%
“…There is, however, some indication that condom behaviors change over time. Parrado et al [23] found that while condom use with FSW was high, it tended to diminish as familiarity with the sex worker grew. A similar pattern was found among migrant farm workers [27] and migrant and marginally housed Latinos in California [28].…”
Section: Latinos and Hivmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, they may lack access to social support and sexual networks that can be found in Latino communities in states with larger, well-established, Latino populations (Apostolopoulos et al, 2006;Hirsch & Yount, 2001;Menjívar, 2000;Vega, Kolody, Valle, & Weir, 1991). The migrant men frequently live with other migrants in shared mobile homes or camp housing in rural areas, or in apartment complexes or houses in urban areas, forming communities in which men may far outnumber women (Grzywacz et al, 2004;Hirsch, Higgins, Bentley, & Nathanson, 2002;Kochhar et al, 2005;Parrado, Flippen, & McQuiston, (Apostolopoulos et al, 2006;Hirsch & Yount, 2001;Viadro & Earp, 2000). Finally, the cyclical movement of migrant men between their countries of origin and rapid growth states, in which the risks of HIV/STD may be high, may contribute to the spread of HIV infection to migrants' wives and other sex partners when they return home.…”
Section: Sociodemographic Characteristics Of Latinos In Rapid Growth mentioning
confidence: 96%
“…Later studies (Bronfman and Minello 1995;Magaña 1991;Organista et al 1997) indicated that temporary migration to the US was associated with a context of loneliness, poverty, emotional crises, risky sex practices, lifestyle changes, and substance use increased migrants' vulnerability to HIV. The lack of social control resulting from living in a more permissive sexual culture with greater access to commercial sex workers and casual partners than in Mexico also increased risk (Parrado et al 2004;Wolffers et al 2002). Studies of migrants residing temporarily in rural areas of the US have highlighted greater vulnerability for HIV among their spouses and stable partners left in Mexico (Hirsch et al 2002(Hirsch et al , 2007Salgado de Snyder 1998).…”
Section: Introductionmentioning
confidence: 95%